Association Between Alcohol Use and Female Sexual Dysfunction From the Data Registry on Experiences of Aging, Menopause, and Sexuality (DREAMS). Issue 2 (21st January 2019) - Kling, Juliana M.; Sidhu, Kimran; Rullo, Jordan; Mara, Kristin C.; Frohmader Hilsaca, Karla S.; Kapoor, Ekta; Faubion, Stephanie S.
Abstract: Introduction: Sexual dysfunction is a common problem in women and the nature of its association with alcohol use remains unclear. Aim: To explore the association between alcohol use and female sexual dysfunction (FSD). Methods: Associations between self-reported drinking and sexual function were evaluated in 2, 253 women presenting for consultation to a women's health specialty clinic. A short version of the Alcohol Use Disorders Identification Test (AUDIT-C) was used to evaluate alcohol use. Women with an AUDIT-C ≥3 were considered at risk for hazardous drinking. Multivariable regression, controlling for depression, anxiety, and abuse (childhood and recent), was used to assess the association between alcohol consumption and FSD (defined as a Female Sexual Function Index [FSFI] ≤26.55 and Female Sexual Distress Scale [FSDS] ≥11) in sexually active women. Main Outcome Measure: The main study outcome measure was the presence of FSD as defined by a score ≤26.55 on the FSFI and ≥11 on the FSDS. Results: 57% of the 1, 649 sexually active women were classified as having FSD; 80% reported any alcohol use and 38% reported drinking patterns with the potential to be hazardous. The women at risk for hazardous drinking had significantly higher FSFI domain scores indicating better sexual function ( P ≤ .001). However, in multivariable analyses, there was no significant difference in the rates of FSD across alcohol use categories in women. Conclusion: In women presenting for consultation to a women's health specialty clinic, an association between alcohol use and FSFI scores was seen, in which greater risk of hazardous drinking was associated with better sexual function scores. However, when sexual distress was included to define sexual dysfunction, those with FSD were not at higher risk of hazardous drinking. Given the complex nature of FSD, additional study is needed to further clarify these relationships.